Clinical outcome comparison of suprapectoral and subpectoral tenodesis of the long head of the biceps with concomitant rotator cuff repair: A systematic review. (February 2022) - Ergün, Selim; Cırdı, Yiğit Umur; Baykan, Said Erkam; Akgün, Umut; Karahan, Mustafa
Background: Simultaneous repairs of rotator cuff and biceps tenodesis can be managed by tenodesis of long head of biceps tendon to a subpectoral or suprapectoral area. This review investigated long head of biceps tendon tenodesis with concomitant rotator cuff repair and evaluated the clinical outcomes and incidences of complications based on tenodesis location. Methods: Medline, Cochrane, and Embase databases were searched for published, randomized or nonrandomized controlled studies and prospective or retrospective case series with the phrases "suprapectoral, " "subpectoral, " "tenodesis, " and "long head of biceps tendon". Those with a clinical evidence Level IV or higher were included. Non-English manuscripts, review articles, commentaries, letters, case reports, and sole long head of biceps tendon tenodesis articles were excluded. Results: From 481 studies, 13 were chosen. In total, 1194 subpectoral and 2520 suprapectoral tenodesis cases were investigated. Postoperative Constant-Murley and American Shoulder and Elbow Surgeons mean scores showed similar good results. In terms of complication incidences, while transient nerve injuries were more commonly seen in patients with subpectoral tenodesis, persistent bicipital pain and Popeye deformity are mostly seen in patients with suprapectoral tenodesis. Discussion: Biceps tenodesis to suprapectoral or subpectoral area with concomitant rotator cuff repair demonstrated similar outcomes. Popeye deformity and persistent bicipital pain were higher in suprapectoral area and transient neuropraxia was found to be higher in subpectoral area. Level of evidence : IV.